Green Fatwa Studies in Global Discourses: Trends and Pathways for the Sustainable Development Agenda - Izudin, Ahmad (UIN Sunan Kalijaga, 2026)
This scoping review explores the trends and pathways in international academic research on green fatwas over the last two decades, from 2007 to 2026. Its goal is to chart how related subjects—especially those indirectly connected to ecological fiqh (fiqh al-bī’ah)—support the wider sustainable development agenda. The study systematically analyzes 37 articles through a comparative review of influential international literature indexed in major academic databases such as Scopus, Web of Science, and Google Scholar, as well as from prominent academic publishers including Springer Nature, Taylor & Francis, Elsevier, Wiley-Blackwell, and SAGE Publications. The results reveal a dynamic but uneven progression marked by thematic diversity, methodological differences, and regional concentration, suggesting that scholarship on green fatwas remains fragmented. Although the field increasingly engages with sustainability discussions, it is still largely framed within normative and ethical perspectives grounded in Islamic legal and theological traditions. Importantly, the study identifies five main thematic clusters that represent key pathways in the field’s development, each linked to specific aspects of the sustainable development agenda: environmental ethics, governance, socio-religious movements, Islamic economic tools, and eco-literacy. As a result, this review offers a structured overview of trends and intellectual developments while emphasizing the need to evolve green fatwas research from a mainly normative focus toward a more practical, evidence-based, and policy-oriented approach within global sustainability governance.